Health And Social Capital Inequalities Among People Affected/ Not Affected By Cancer, Referring To Cancer Institute Of Tehran - Mohamad Tavakol; Mohsen Naseri Rad (Tehran University of Medical Sciences, 2012)
Background and Aim: Social capital is one of the social determinants of health, which might have an important role in health inequalities. The amount of social capital gained by individuals differs depending on social circumstances in fact, not all individuals can equally benefit from social resources of social capital. This study aims to examine the effect of social capital dimensions on being afflicted by cancer in patients referring to Cancer Institute of Tehran. Materials and Methods: This is an analytic-descriptive study, the population of which included all patients aged over 14 and affected by stomach, colon and breast cancers, referring to Cancer Institute of Tehran University of Medical Sciences, Tehran, Iran. The sample consists of 106 subjects who have been chosen using the classified probability sampling method. The data collection device was a questionnaire together with a structured interview. Social capital emphasizes the two structural and cognitive dimensions. Moreover, it stresses personal social capital. Results: Health inequalities and cancer are the results of simultaneous interaction between the different dimensions of social capital and behavioral/psychological and biological factors. People enjoying similar social capital in life experience cancer-related stress and unhealthy behavior in different ways Conclusion: An increase or decrease in any of the social capital components can lead to a change in the number of those getting the disease.